Estudos longitudinais da influência do veículo na eficácia da pasta de hidróxido de cálcio em infecções endodônticas: revisão sistemática - Decurcio, Daniel de Almeida (2007)
Longitudinal studies about the influence of the vehicle on the efficacy of calcium hydroxide pastes in endodontic infections were studied through a systematic review. Bibliographic tabulation sources identified electronically by MEDLINE, since 1966 until January 2nd of 2007 and Cochrane Library, on the same period, were used. As searching strategy the following terms were used in different combinations: calcium hydroxide, chlorexidine, root canal infection, faecalis, intracanal dressing, endodontic infection, intracanal medicament, paramonochlorophenol, paramonochlorophenol or p-monochlorophenol. The studies were selected by two independent reviewers that also determined the inclusion and exclusion criteria. The search presented 303 related articles, and from these, 22 articles were literature reviews, 71 articles were related to in vivo studies (humans or animals), 34 studies were cases reports, and 178 included in vitro studies. From the 71 in vivo studies, 5 studies satisfied the inclusion criteria, what enabled the data analysis. The impossibility of results combination caused by the methodology differences of the studies did not allow the execution of meta-analysis. In vitro studies showed that the vehicle influences the chemical characteristics of the calcium hydroxide paste on what concerns to the speed of diffusion an ionic dissociation, like occurs with aqueous Hydro-solvable vehicles. This chemical characteristic reflects on the antimicrobial potential. On the five studies in humans that satisfied the inclusion criteria for analysis of scientific evidence, from a total of 110 teeth with endodontic infections, after the sanitization process combined with the calcium hydroxide paste associated to saline solution, in 35 teeth were detected microorganisms on the final samples. The saline solution was the only vehicle present in all the included studies, what limited comparisons. Considering the estimative of clinical success, the adequate sanitization process assisted by the calcium hydroxide paste with aqueous vehicle reduces the endodontic microorganisms, what favors the prognostic.